Pengaruh Reward Terhadap Minat Belajar Nilai Agama Dan Moral Anak di TK - Berahima, Sri Yuniken; Us. Djuko, Rapi; Jamin, Nunung S. (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This research is experimental quantitative research. The result found a significant difference in the average pretest and posttest with a total of 20 students, which can prove the average value of the pretest data. pre-test data shows that the highest score is 20 and the lowest is 12. After analysis, the average value is 17.95, and the standard deviation is 2.2355. Meanwhile, post-test data shows the highest score is 40 and the lowest score is 32, and after analysis, the average value is 37.45, and the standard deviation is 2.7810. This demonstrates that the research sample obtained an increase in average results from the initial and final tests. Thus, this hypothesis study stated that there is an influence of rewards on interest in learning religious and moral values ​​of children in TK. Rewards are a big attraction for children to continue participating in learning activities about religious and moral values, especially understanding prayer.